The Middle-Eastern Cold War: The religious struggle between the kingdom of Saudi Arabia and the Islamic Republic of Iran - Zein, Omar (AUC Knowledge Fountain, 2015)
The Middle East has witnessed in the past two decades an increase in the number of internal conflicts within many states. Many of those internal conflicts had developed into a religious strife between Sunnis and Shi’as. Today in Iraq, Syria, Yemen and Bahrain there is an ongoing conflicts between representatives of both sects; whether it is a state or transnational actors. The Middle East has not witnessed a struggle between the two most popular sects of Islam since the Ottoman-Safavid war in 16th century. To analyze the cause behind the rise in conflicts between Sunnis and Shiites; there must be an examination of the states and religious actors that contributed to the rise of this conflict. Therefore, this paper attempts to study each of Saudi Arabia and Iran; as they had played a large role in supporting Islamist movements in the Middle East. The relationship between both Saudi Arabia and Iran before the Islamic Revolution had managed to stabilize the relationship between Sunnis and Shi’as. However, a change of the Iranian regime’s identity and its Shiite Islamization had sparked a tension between Saudi Arabia and Iran. Later, the conflict between both states had moved into other states such as Syria, Iraq, Bahrain and Yemen. In order to analyze the impact of religious identity on the struggle between the two states; the paper examines each states’ identity formation, their linkage to other religious Islamist movement and how it contributed to an increase in internal conflicts in the Middle East.